2016
DOI: 10.1161/circulationaha.115.018042
|View full text |Cite
|
Sign up to set email alerts
|

Pathobiological Determinants of Atherosclerosis in Youth (PDAY) Risk Score in Young Adults Predicts Coronary Artery and Abdominal Aorta Calcium in Middle Age

Abstract: Background We explored whether, the Pathobiological Determinants of Atherosclerosis in Youth (PDAY) coronary and abdominal risk scores measured at ages 18–30 years and changes in these scores would more strongly predict coronary artery calcium (CAC) and abdominal aortic calcium (AAC) assessed 25 years later, than scores measured 25 years later. Methods and Results In the Coronary Artery Risk Development in Young Adults study, 3008 participants had measurements of risk score components at 5 year intervals beg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(35 citation statements)
references
References 32 publications
1
30
1
3
Order By: Relevance
“…The integrated 10‐year Framingham Risk Score (FRS), informing on the estimated risk of cardiovascular events, has been calculated for all participants . Furthermore, we computed the Pathobiological Determinants of Atherosclerosis in Youth (PDAY) risk score; given the wide range of age of our population, the PDAY risk score was computed from the modifiable risk factors, as previously reported …”
Section: Methodsmentioning
confidence: 99%
“…The integrated 10‐year Framingham Risk Score (FRS), informing on the estimated risk of cardiovascular events, has been calculated for all participants . Furthermore, we computed the Pathobiological Determinants of Atherosclerosis in Youth (PDAY) risk score; given the wide range of age of our population, the PDAY risk score was computed from the modifiable risk factors, as previously reported …”
Section: Methodsmentioning
confidence: 99%
“…Lo descrito habla del conjunto de factores determinantes de las dislipidemias, teniendo en cuenta factores del medio ambiente, del estilo de vida, la genética y calidad de atención de los servicios de salud 18 . Así mismo, estudios de cohortes han mostrado que la presencia de dislipidemias en población pediátrica y adolescente, perdura en la edad adulta y se asocia a enfermedad cardiovascular futura [19][20][21][22][23] . En España, las comunidades de Aragón, Castilla-León, Cataluña, La Rioja, Madrid, Navarra y País Vasco ya incluyen el diagnóstico genético en sus estrategias de detección de la hipercolesterolemia familiar.…”
Section: Introductionunclassified
“…There is a strong association between the PDAY risk score measured in young adulthood and the presence and severity of coronary atherosclerosis in middle age (Gidding et al, 2016).…”
Section: Behavioural Factors Depression Can Change a Person's Cognitmentioning
confidence: 99%
“…Many studies have shown that risk factors measured in adolescents and early adulthood predict atherosclerosis in adults aged 30 to 45 years (Gidding et al,20 16). The physiological risk factors for atherosclerosis in middle age were measured using pathobiological determinants of atherosclerosis in youth (PDAY) scores, which measures age, gender, non-HDL cholesterol, HDL cholesterol, smoking, blood pressure, obesity and hyperglycemia (Gidding et al, 2016). As each risk factor is added, a one-point increase in the score is also added.…”
Section: Behavioural Factors Depression Can Change a Person's Cognitmentioning
confidence: 99%
See 1 more Smart Citation